2019
DOI: 10.1002/smtd.201900731
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring Small Energy Storage Change of Electrochromic Supercapacitors via Perovskite Photodetectors

Abstract: In situ monitoring the healthy state of energy storage devices is a smart way to avoid severe accidents and major emergencies. Electrochromic supercapacitors (ECSCs) stand out among other devices owing to the smart color variation during charge and discharge processes. However, it is hard to obtain the precise state of charge via only identifying their color change. To address this problem, an integral system composed of the inorganic CsPbBr3 perovskite photodetector (PPD) and polyaniline (PANI)//WO3 ECSC is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…They achieved quantitative monitoring of device by getting the linear link of ESL and the optical density at the wavelength of 600 nm. Moreover, Sun et al [ 178 ] successfully achieved the in-situ monitoring of the ESL of bifunctional device constantly and accurately with the help of an inorganic CsPbBr 3 perovskite photodetector, based on the PANI//WO 3 bifunctional ECESD they reported earlier ( Figure 15 e). This photodetector detects according to the change of response current to a green laser with the wavelength of 520 nm penetrated through the bifunctional device.…”
Section: Electrochromic Energy Storage Devices (Ecesds)mentioning
confidence: 97%
See 1 more Smart Citation
“…They achieved quantitative monitoring of device by getting the linear link of ESL and the optical density at the wavelength of 600 nm. Moreover, Sun et al [ 178 ] successfully achieved the in-situ monitoring of the ESL of bifunctional device constantly and accurately with the help of an inorganic CsPbBr 3 perovskite photodetector, based on the PANI//WO 3 bifunctional ECESD they reported earlier ( Figure 15 e). This photodetector detects according to the change of response current to a green laser with the wavelength of 520 nm penetrated through the bifunctional device.…”
Section: Electrochromic Energy Storage Devices (Ecesds)mentioning
confidence: 97%
“…( e ) Basic structure and mechanism of the in situ monitoring system composed of PANI//WO 3 ECSCs and CsPbBr 3 perovskite photodetector. Adapted with permission from [ 178 ]. Copyright John Wiley and Sons, 2019.…”
Section: Figurementioning
confidence: 99%
“…A novel nanorod-like morphology of a Ba x Mn 1− x O 3 perovskite oxide electrode has attracted great attention in boosting the electrochemical properties and the favorable electrode materials for the development of supercapacitor applications (specific capacitance value of 433 F g −1 with good cyclic stability) [ 47 ]. Sun’s group constructed a PANI/WO 3 composite as an active electrode material for an electrochromic supercapacitor; their common energy-storage devices can be clearly estimated by the charge–discharge process [ 48 ]. Moreover, Fan et al [ 49 ] demonstrated an asymmetric supercapacitor withKNiF 3 @ CNTs−8 as a positive electrode and activated carbon (AC) as a negative electrode via the solvothermal method.…”
Section: Perovskite-based Nanocomposite In Supercapacitor Applicationsmentioning
confidence: 99%
“…Indeed, reports on such a kind of integrated electrochromics device are increasing in recent years. [ 87–94 ]…”
Section: Printing Technologies For Energy Storage Applicationsmentioning
confidence: 99%